Development of Noxological Culture Among Students for Teaching Occupational Safety and Health and Wellness in Pedagogical Institutions of Higher Education - Lesіa V. Kravchenko (Mukachevo State University, 2021)
The development of noxological culture among students of pedagogical educational institutions is an urgent problem since it is associated with the state of protection of the individual and society from internal and external threats in everyday life. The purpose of the study was to analyse the discipline "Occupational Safety and Health and Wellness", which plays an important role in understanding potential dangers associated with human activity and forms risk-oriented thinking. In the course of the study, the following methods were used to establish the relationship of noxological culture with the health and wellness of future teachers: elementary theoretical analysis and synthesis of factual material, axiomatic method, and generalisation. The concepts of noxology and noxological culture of the individual were considered. As a result of the study, it was determined that noxological culture is an important structural component of health and wellness, and is also an integral component of the professional culture of each future specialist. The important role of the discipline "Occupational Safety and Health and Wellness" in the development of students' noxological culture was determined. The components of noxological competence were considered. The study covered an important role of pedagogical higher education in forming scientifically sound criteria for possible risk. The study of the above-mentioned discipline forms a system of knowledge about the nature of dangers, their features and ways to reduce risk and their occurrence